Users’ experience in role-playing game: measuring the player's gameplay experience - Ahmad, Ibrahim; Jaafar, Azizah; Othman, Mohd Fairuz Iskandar; Makina, Tarisa (Universiti Teknologi Malaysia, 2015)
This study is related to the users’ gaming experience which is gained through a set of users’ activities to play computer games. The activities are designed based on the features of games that are desired by the users. As a result, the RPG computer games have been designed and user gaming experience via questionnaire has been tested. There are seven constructs measuring the immersive, flow, competence, tension, challenge, positive affect and negative affect. The results showed the constructs that lead to positive values is indicated by the mean value for the user’s gaming experience is very good, and vice-versa for the mean construct geared negative value.